2014
DOI: 10.1038/srep06954
|View full text |Cite
|
Sign up to set email alerts
|

Energy barrier at the N719-dye/CsSnI3 interface for photogenerated holes in dye-sensitized solar cells

Abstract: This report is to address the question if black γ-polymorph of cesium tin tri-iodide (B-γ-CsSnI3) can be used as a solid-state hole-transport material in the conventional DSSCs with the N719 dye to replace the liquid electrolyte as reported by I. Chung et al. on Nature 485, 486, (2012). Here we demonstrate rigorously that B-γ-CsSnI3 is not energetically possible to collect photogenerated holes because of the large energy barrier at the interface of N719/B-γ-CsSnI3. Therefore, it cannot serve as a hole-transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 17 publications
11
100
2
Order By: Relevance
“…2b) and n is ~10 . These theoretical results seem to explain the experimental results reported to date; i.e., the electrical properties of Cs2SnI6 ranging from insulating 18 to low-density n-type conduction (n ~110 14 cm…”
Section: +supporting
confidence: 84%
See 1 more Smart Citation
“…2b) and n is ~10 . These theoretical results seem to explain the experimental results reported to date; i.e., the electrical properties of Cs2SnI6 ranging from insulating 18 to low-density n-type conduction (n ~110 14 cm…”
Section: +supporting
confidence: 84%
“…On the other hand, Cs2SnI6 have not shown p-type conductivity unlike the other Sn 2+ -based compounds and have shown ntype conduction or insulating behavior depending on the synthetic routes. Lee et al 13 reported the native n-type conduction with electron density (n) of ~110 14 cm 3 in polycrystalline Cs2SnI6 pellets annealed at 200 o C, while Zhang et al 18 observed very high resistivity in room temperature-processed Cs2SnI6. Therefore, in order to clarify the intrinsic nature of Cs2SnI6 and its origin, a systematic theoretical study on the intrinsic defects is important, which will provide a guiding principle for tuning its properties for photovoltaic and other semiconductor applications.…”
Section: +mentioning
confidence: 99%
“…For this work, to reflect the general synthesis reaction of halide perovskites (i.e., AX + BX 2 → ABX 3 ), 17,21,22 here we simply use i as the bulk components CsI, RbI, and SnI 2 , respectively, rather than atomic species Cs, Rb, Sn, and I.…”
Section: Methodsmentioning
confidence: 99%
“…One of the promising alternatives of Pb (II) is Sn (II), which has been demonstrated in bulk and thin films for solar cell applications ,. The single crystals of MASnI 3 and FASnI 3 are found to be p‐type and n‐type semiconductors respectively with the trap densities in the order of 10 11 cm −3 .…”
Section: Tin Perovskitesmentioning
confidence: 83%